2013
DOI: 10.1155/2013/273102
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Spectrophotometric Method for the Simultaneous Determination of Amlodipine, Valsartan, and Hydrochlorothiazide in Coformulated Tablets

Abstract: A new, simple and specific spectrophotometric method was developed and validated in accordance with ICH guidelines for the simultaneous estimation of Amlodipine (AML), Valsartan (VAL), and Hydrochlorothiazide (HCT) in their ternary mixture. In this method three techniques were used, namely, direct spectrophotometry, ratio subtraction, and isoabsorptive point. Amlodipine (AML) was first determined by direct spectrophotometry and then ratio subtraction was applied to remove the AML spectrum from the mixture spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…There are reported methods for the determination of AML, ALI or HCT in different dosage forms [27][28][29][30][31]. AML, ALI and HCT were simultaneously determined in their ternary mixture by HPLC and capillary electrophoresis [32,33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reported methods for the determination of AML, ALI or HCT in different dosage forms [27][28][29][30][31]. AML, ALI and HCT were simultaneously determined in their ternary mixture by HPLC and capillary electrophoresis [32,33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ternary mixtures suffer a higher degree of difficulty in spectrophotometric resolution than binary mixtures, due to the severe overlap usually noticed in their spectra. Many methods have been developed for resolution of the overlapped spectra of ternary mixtures using different spectrophotometric and chemometric techniques [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…AML and VAL are official in BP and USP [2,3]. Literature review showed that few analytical methods have been described for the estimation of AML and VAL including spectrophotometric [4][5][6][7], highperformance liquid chromatography (HPLC) [8][9][10][11][12][13][14], spectrofluorimetric method [15][16][17], electrochemical and voltammetric methods [18][19][20][21][22] had been reported for the estimation of AML and VAL in pure or in dosage forms. According to the best of my knowledge, there is no Stability indicating new-RP-HPLC method for simultaneous determination of Amlodipine Besylate, Valsartan and its related substances in their film-coated tablets dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…There are reported methods for the determination of BIS or HCT in different dosage forms [47][48][49][50] and in their binary mixtures [45,[51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Many reported methods were reported for the determination of AML, ALI or HCT in different dosage forms [57][58][59][60][61][62]. HPLC and capillary electrophoresis methods were reported for simultaneous determination of this ternary mixture [63,64].…”
Section: Introductionmentioning
confidence: 99%